Katutubo glimpses of Philippine indigenous culture (Makati City Filipinas Heritage Library, Ayala Foundation, 2000)
Presents four indigenous communities in four different destinations across TInguian in the province of Abara; the Agta of Isabela in the Pacific side of the archipelago ; The T`boli of Lake Sebu in South Cotabato; The Hanunuo-Mangyan on the island of Mindoro.
CDROM
English translation of : Katutubo : sulyap sa mga katutubong kultura ng pilipinas.
Keywords: Ethnic groups -- Philippines; Philippines -- Social life and customs